The Influence of Management Domain on Financial Business Processes in Official Regional Apparatus Organization of Banten Province - Ahmad Hafiz Ismail; Hamzah Ritchi; Zaldy Adrianto (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study examines the effects of the risk management of electronic based government systems, data management, IT asset management on the quality of financial business processes in the regional apparatus organization of the Province of Banten Methodology:  The research uses quantitative research method.  This study used a questionnaire to collect data and supplemented by interviews with division SPBE in Diskominfo. The data analyzed using Structural Equation Modeling Partial Least Square with help of software Smart PLS version 4.1.0.9. Results/findings: Risk management of electronic based government systems, data management, IT asset management positively affect financial business processes. Conclusions: SPBE risk management, data management and ICT asset management has a positive and significant effect on the quality of financial business processes. Limitations: Recommendations for future research are to add variables in the management domain or other domains. Contribution: This research advances our knowledge and comprehension of e-government in Indonesia, especially in local government.